The Role of Southeast Sulawesi PPPKMI in Strengthening Health Promotion Strategies As a Covid-19 Response Effort - Rahmawati Ramadhan; Hartati bahar; Fikki Prasetya (MIRACLE Journal Of Public Health, 2021)
Covid-19 is now one world pandemic and efforts health promotion strategies have a very large role to prevent the spread of Covid-19. PPPKMI is a professional organization of health promotion workers who play an important role in strengthening health promotion strategies in Southeast Sulawesi in efforts to overcome Covid-19 . The purpose of this study was to determine the role of the Southeast Sulawesi PPPKMI professional organization in strengthening health promotion strategies as an effort to overcome Covid-19. This type of study is a qualitative study with a phenomenological approach using data collection techniques through observation and in-depth interviews, tracing documents and processed by content analysis. Research informants are PPPKMI administrators, PPPKMI partners, and health promotion workers under the PPPKMI professional organization. According to the results of the study, it was found that the empowerment activities carried out by PPPKMI consisted of self-efficacy and health literacy. Atmosphere Development, consisting of appraisal support, tangiable support, self-esteem support. Advocacy is carried out by providing recommendations to local governments with various prevention recommendations so that this pandemic does not spread further. Therefore, the conclusion of this study is PPPKMI professional organization in strengthening health promotion strategies as a Covid-19 response effort in Southeast Sulawesi in 2021 is carried out using three ways, namely empowerment activities, atmosphere building activities and advocacy activities. All activities are carried out by PPPKMI According to important tasks and goals of activity according to the established laws.